COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN DESA WISATA TANJUNG PUNAK KECAMATAN RUPAT UTARA KABUPATEN BENGKALIS TAHUN 2023 - Amira, Yuni; Wasillah, Asiah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research discusses collaborative governance to see how the collaboration of the Tanjung Punak Village Government and tourism awareness groups with the Bengkalis Regency Tourism Office, Bengkalis Regency Tourism UPT, Pertamina Hulu Rokan, and Riau Tourism College, because Tanjung Punak Village is one of the villages that has been issued a tourism village decree by the Bengkalis regent, and won 1st place in the Anugerah Desa Wisata Indonesia (ADWI) Riau Province in 2023, but in 2023 it also experienced a decrease in the number of tourist visits and facilities and infrastructure at tourist attractions that were less well maintained after being built. Therefore, this research aims to find out the collaboration between the actors involved in the development of Tanjung Punak Tourism Village in 2023. The research methodology that researchers use is descriptive qualitative method with the type of data used is primary data obtained through interviews and secondary data obtained from documents related to the research. The author uses the theory of Emerson, Nabatchi, & Balogh (2012) about the collaborative governance regime (CGR) which consists of 3 components, namely collaboration dynamics, collaborative actions and temporary impacts and adaptations. Based on the results of the research that has been conducted, it shows that collaborative governance in the development of Tanjung Punak Tourism Village in 2023 is not optimal. This is evidenced by the role of collaborative actors, not all of which have been well implemented. Collaboration between Tanjung Punak Village with Pertamina Hulu Rokan and the College of Tourism which provides a good temporary impact and adaptation for Tanjung Punak Village and the village community. Meanwhile, the collaboration between the Tanjung Punak Village Government and the Tanjung Punak Village Tourism Awareness Group does not agree with the Bengkalis Regency Tourism Office and the North Rupat District Tourism UPT regarding conflicts over the management of Tanjung Lapin tourism potential in Tanjung Punak Village. The Tanjung Punak Village community, not all of whom are interested and participate in the collaboration of tourism village development, making village development not optimal. Keywords: Collaborative Governance, Development, Tourism Village.